Comparative evaluation of hysterosalpingo contrast sonography with laparoscopy for determination of tubal patency in infertility - Krishnamoorthy, Geetha; Perumal, Amutha; Boovaragasamy, Chithra; Gnanasabai, Gnanamani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Tubal factor is responsible for infertility and is found in one of three infertile women. The current research was undertaken to compare the efficacy of hysterosalpingo contrast sonography (HyCoSy) with laparoscopy and chromopertubation in infertile women. Methods: A cross-sectional study was conducted from August 2016 to March 2017 among the patients attending outpatient department with complaints of primary or secondary infertility after obtaining written and informed consent. Detailed history of the patient was taken; clinical examination and necessary investigations were done. Data analysis was carried out using SPSS version 22. Results: All the HyCoSy findings showed excellent specificity (84-100%) and the sensitivity ranged from 40-87%. Conclusions: Study conclude that HyCoSy is a good screening method for evaluating uterine cavity lesions and tubal block in infertile women being safe, sensitive, cost effective, non-invasive procedure giving additional information regarding ovarian, adnexal and peritoneal pathology.